Phenome-wide association studies demonstrating pleiotropy of genetic variants within FTO with and without adjustment for body mass index - Cronin, Robert M.; Field, Julie R.; Bradford, Yuki; Shaffer, Christian M.; Carroll, Robert J.; Mosley, Jonathan D.; Bastarache, Lisa; Edwards, Todd L.; Hebbring, Scott J.; Lin, Simon; Hindorff, Lucia A.; Crane, Paul K.; et al. (Frontiers in Genetics, 2014)
Phenome-wide association studies (PheWAS) have demonstrated utility in validating genetic associations derived from traditional genetic studies as well as identifying novel genetic associations. Here we used an electronic health record (EHR)-based PheWAS to explore pleiotropy of genetic variants in the fat mass and obesity associated gene (FTO), some of which have been previously associated with obesity and type 2 diabetes (T2D). We used a population of 10,487 individuals of European ancestry with genome-wide genotyping from the Electronic Medical Records and Genomics (eMERGE) Network and another population of 13,711 individuals of European ancestry from the BioVU DNA biobank at Vanderbilt genotyped using Illumina HumanExome BeadChip. A meta-analysis of the two study populations replicated the well-described associations between FTO variants and obesity (odds ratio [OR]=1.25, 95% Confidence Interval=1.11-1.24, p=2.10 x 10 9) and FTO variants and T2D (OR=1.14, 95% CI=1.08-1.21, p=2.34 x 10 6). The meta-analysis also demonstrated that FTO variant rs8050136 was significantly associated with sleep apnea (OR=1.14, 95% CI=1.07-1.22, p=3.33 x 10 5); however, the association was attenuated after adjustment for body mass index (BMI). Novel phenotype associations with obesity-associated FTO variants included fibrocystic breast disease (rs9941349, OR=0.81, 95% CI=0.74-0.91, p=5.41x10 5) and trends toward associations with nonalcoholic liver disease and gram-positive bacterial infections. FTO variants not associated with obesity demonstrated other potential disease associations including noninflammatory disorders of the cervix and chronic periodontitis. These results suggest that genetic variants in FTO may have pleiotropic associations, some of which are not mediated by obesity.